Pulmonary Aspergillosis, an approach to clinical and radiological manifestations. Report of three cases: Manifestaciones clínicas y radiológicas de la Aspergilosis Pulmonar: Informe de tres casos - Barrios Taborda, Onaldo José (2024)
Pulmonary aspergillosis, caused by the opportunistic fungus Aspergillus, primarily affects immunocompromised individuals. This report presents three cases: An 18-year-old female with acute leukemia developed respiratory distress and bilateral "tree-in-bud" patterns on CT. Despite voriconazole treatment, she succumbed to respiratory failure. A 58-year-old female with diabetes and COPD had dyspnea and hemoptysis. Imaging revealed a cavitated lesion, confirming aspergilloma. Surgery was considered due to active hemoptysis. A 41-year-old female with a history of tuberculosis presented with fever and respiratory symptoms. CT showed cavitated lesions and bronchiectasis, confirming chronic aspergillosis. She responded well to voriconazole. These cases highlight the variability in pulmonary aspergillosis and underscore the importance of timely diagnosis and treatment to improve patient outcomes.